The changing risk perception towards nuclear power in China after the Fukushima nuclear accident in Japan. (September 2018) - Huang, Lei; He, Ruoying; Yang, Qianqi; Chen, Jin; Zhou, Ying; Hammitt, James K.; Lu, Xi; Bi, Jun; Liu, Yang
Abstract: Gradual recovery of Chinese nuclear power industry and its increasingly important position in the world have created a need to understand how public attitudes towards nuclear power changed after the Fukushima nuclear accident in Japan (FNAJ). To address this need, we augment our previous work to include data from a new survey conducted three years after the FNAJ in the same study area. The results showed that three years after the FNAJ, factor knowledge continued to increase, whereas the other four perception factors acceptance, risk, benefit, and trust had recovered from their post-FNAJ changes to different degrees. The sensitive groups whose acceptance declined more after the FNAJ showed a greater increase as time passed. It was also found that median acceptable frequency for level 1 nuclear events (anomaly) showed little change from Survey 2 to Survey 3, while tolerance of more severe events (incidents and serious incidents) has decreased substantially. The overall recovery of public acceptance shown in our study was in line with the nuclear development trend of China. But more efforts still need to be made to improve nuclear safety and risk communication. Highlights: Nuclear risk perception had recovered to different degrees except factor knowledge. People oppose nuclear power stations in their own city more than before the FNAJ. People whose acceptance declined sharply after the FNAJ but also recovered greatly. Tolerance of incidents and serious incidents had decreased substantially.